2016
DOI: 10.1016/j.eururo.2015.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Size-adjusted Quantitative Gleason Score as a Predictor of Biochemical Recurrence after Radical Prostatectomy

Abstract: Background The risk of biochemical recurrence (BCR) following radical prostatectomy for pathologic Gleason 7 prostate cancer varies according to the proportion of Gleason 4 component. Objective We sought to explore the value of several novel quantitative metrics of Gleason 4 disease for the prediction of BCR in men with Gleason 7 disease. Design, setting, and participants We analyzed a cohort of 2630 radical prostatectomy cases from 1990–2007. All pathologic Gleason 7 cases were identified and assessed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Subsequent to the 2014 Consensus Conference, studies have demonstrated that increasing percent pattern 4 at RP correlates with an increased risk of biochemical recurrence after RP. 42,50,51 There have also been several publications showing that percent pattern 4 on needle biopsy can improve prediction of upgrading at RP and of adverse findings at RP and biochemical recurrence after RP. 52,53 General applications of the Gleason grading system…”
Section: Reporting Percentage Patternmentioning
confidence: 99%
“…Subsequent to the 2014 Consensus Conference, studies have demonstrated that increasing percent pattern 4 at RP correlates with an increased risk of biochemical recurrence after RP. 42,50,51 There have also been several publications showing that percent pattern 4 on needle biopsy can improve prediction of upgrading at RP and of adverse findings at RP and biochemical recurrence after RP. 52,53 General applications of the Gleason grading system…”
Section: Reporting Percentage Patternmentioning
confidence: 99%
“…At present, there are many clinicopathological parameters to evaluate the risk of progression, metastasis and prognosis of PCa. The risk factors for biochemical recurrence included body mass index, preoperative PSA, the proportion of positive biopsy cores, pathological stage, extracapsular extension, seminal vesical invasion, lymph node metastasis, and positive surgical margin . However, the accuracy of these traditional clinicopathological factors for predicting the biochemical recurrence of PCa remains low .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the quantity of GP 4/5 provides additional prognostic significance. [6][7][8][9][10] Cole et al 10 reported that the incremental percent of GP 4 component in biopsies was an important predictor of adverse pathology and prostate-specific antigen recurrence across the entire range of GS 3 þ 4, 4 þ 3, and 4 þ 4 PCa. The quantity of GP 4 has been used in determining candidacy for active surveillance and for selection of different radiation therapy protocols.…”
Section: Discussionmentioning
confidence: 99%
“…There have been continued efforts in improving the Gleason system for risk stratification. 9 Permutations of the Gleason system have been exploited to enhance risk stratification, such as quantification of Gleason grade 4/ 5. [11][12][13][14][15] Several recent studies show that cribriform pattern is the worst of all GP 4 morphologies (others being poorly formed glands and fused glands) and independently predicts biochemical recurrence and risk of distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation